Effect of forest fires on forest plant complexes contaminated by radionuclides - L. D. Romanchuck; V. I. Ustymenko (Ядерна фізика та енергетика)
Among the most pressing threats to the existence of forest plant complexes of the nature reserve fund is the pyrogenic danger, which is exacerbated by changes in the natural hydrolytic regime and global climate change, the driving effects of which are currently difficult to fully assess. The article highlights the results of a study of the forest plant complexes and soil state of the nature reserve "Drevlyanskyi" in Zhytomyr region after the fires. The results of the field survey of plantations, agrochemical and radiological analysis of soil indicators are presented. Studies show a change in the composition of forest plant complexes, a reduction in the number of herbaceous species, and a decrease in the area of moss and lichen cover. The surveyed area is characterized by significant spatial heterogeneity of the main agrochemical and physicochemical parameters of the soil. There was a slight increase in the content of heavy metals in the soil, however, the indicators did not exceed the maximum allowable concentrations in these areas. To assess the radiation situation after fires on the territory of the nature reserve, the indicators of the density of soil pollution with 137Cs and 90Sr were determined. The authors recommended a set of measures to improve the efficiency of nature reserves. Adherence to the recommendations will help to increase the environmental sustainability of forest plant complexes and will minimize the occurrence of fires and their consequences.